PENGEMBANGAN BUKU AJAR KEWIRAUSAHAAN PADA PERKULIAHAN PEMBELAJARAN DARING KOLABORATIF (PDK) - Rochsun; Alfiana Patricia, Firda; Putri Anugraini, Asri; Avianty, Donna; Peni, Natalia (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2024)
Developing textbooks is an important part of the education system which aims to support and facilitate the learning process. The method used in this research is Research and Development (R&D) development which aims to develop teaching materials in the form of Entrepreneurship textbooks used in Collaborative Online Learning lectures. The textbooks that have been developed are then tested in learning. The development research procedure uses a 4D model. There are 4 steps in the 4D model, namely, the Define stage, the Design stage, the Development stage and the Dessiminate stage. The use of entrepreneurship teaching materials for students is appropriate, because in terms of format, material content and language it is rated as suitable for use as teaching materials for students in the learning process.